Targeting gut microbial bile salt hydrolase (BSH) by diet supplements: new insights into dietary modulation of human health. Issue 14 (29th June 2022) - Yang, Yanan; Wu, Chongming
Abstract : Dietary supplements could modulate the abundance of BSH-producing bacteria to regulate the BSH enzyme activity, thereby change the BAs composition to regulate FXR signaling, which then regulate human health. Abstract : The gut microbiome is increasingly recognized as a vital organ that participates in nutrient acquisition, energy regulation and maintenance of human health. Targeted manipulation of the gut microbiota by dietary supplements has been validated as an effective approach to improve human health. Among various gut microbiome–host interactions, bile acids (BAs) are intensively metabolized by the gut microbes and control a variety of metabolic processes such as energy homeostasis, glucose and lipid metabolism by activation of farnesoid X receptor (FXR). How dietary supplements regulate FXR signaling and promote human health is thus attracting broad interest and well-reviewed. However, the exact effects of BAs on FXR activity and host metabolism are compound-specific. Different BAs are metabolized by the gut microbes into varied BA derivatives and then impose distinct modulation of FXR activity and host health. As the gateway enzymes, bile salt hydrolases (BSHs), produced by the gut microbiota, control the first step of BA transformation in the gut. Therefore, BSH is a key mediator linking the food supplements' modulation to the gut microbiota and BAs-FXR signaling. In this review, we generalized the relationship between BAs, gut microbial BSHs and FXR, and summarized the dietary regulators of BSH and FXR activities, aiming to rationalize the dietary management of human health via dietary supplement—gut microbiota—FXR signaling axis.